Customary law and justice: Protecting the rights of women victims of sexual violence in Bali - Rai Yuliartini, Ni Putu; Sudika Mangku, Dewa Gede; Kbarek, Lukas Norman (Universitas Ahmad Dahlan, 2024)
Introduction to The Problem: The disparities in societal roles often manifest as systemic inequality, rooted in a patriarchal culture that positions men in a dominant role while undermining the concept of women as equals. Gender-based discrimination is intricately woven into the fabric of society, perpetuated through entrenched social customs, traditions, child-rearing practices, educational systems, and the differentiation of social responsibilities assigned to men and women. Purpose/Objective of Study: This study aims to investigate and critically analyze the characteristics of sexual violence experienced by women within Bali's customary law communities, with a focus on mechanisms for restoring legal capacity. It further explores the interplay between statutory regulations and customary practices to enhance equitable legal protections for victims of sexual harassment. Design/Methodology/Approach: This study applies a sociolegal approach, combining statutory, comparative, conceptual, and sociological methods. Primary and secondary data were analyzed using legal hermeneutics, interpreting regulations within their context to examine the rights of women victims of sexual violence. The research highlights justice and cohesion within customary law communities in the fulfillment of these rights. Findings: First, the forms of sexual violence perpetrated against women within customary law communities in Bali—specifically in the traditional villages of Sudaji, Undisan Kelod, Munti Gunung, and Angantelu—were predominantly instances of rape and familial sexual relations (incest). Second, the findings highlight the integration of statutory regulations with customary law to enhance equitable legal protections for women affected by sexual violence within these communities. This integration focuses on measures for comprehensive restoration, including restitution, compensation, assurances of victim satisfaction, rehabilitation, and guarantees for the prevention of recurrent offences. Paper Type: Research Article